2012
DOI: 10.1152/ajpregu.00606.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reno-protective mechanisms of epoxyeicosatrienoic acids in cardiovascular disease

Abstract: Cardiovascular disease (CVD) is the leading cause of mortality worldwide, and it is well known that end-stage renal disease (ESRD) is a profound consequence of the progression of CVD. Present treatments only slow CVD progression to ESRD, and it is imperative that new therapeutic strategies are developed to prevent the incidence of ESRD. Because epoxyeicosatrienoic acids (EETs) have been shown to elicit reno-protective effects in hypertensive animal models, the current review will focus on addressing the reno-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 130 publications
(185 reference statements)
3
65
1
Order By: Relevance
“…There is a phenomenal amount of data demonstrating the importance of the P450/sEH axis in renal physiology and the ability of EETs to increase renal blood flow and the glomerular filtration rate as well as to decrease renal vascular resistance, as reviewed extensively elsewhere Elmarakby, 2012;Capdevila and Wang, 2013). In the kidney, EETs and 20-HETE are also produced in the proximal tubule, the thick ascending loop of Henle, and the cortical collecting duct, where they modulate ion transport.…”
Section: Regulation Of Blood Pressurementioning
confidence: 99%
“…There is a phenomenal amount of data demonstrating the importance of the P450/sEH axis in renal physiology and the ability of EETs to increase renal blood flow and the glomerular filtration rate as well as to decrease renal vascular resistance, as reviewed extensively elsewhere Elmarakby, 2012;Capdevila and Wang, 2013). In the kidney, EETs and 20-HETE are also produced in the proximal tubule, the thick ascending loop of Henle, and the cortical collecting duct, where they modulate ion transport.…”
Section: Regulation Of Blood Pressurementioning
confidence: 99%
“…The pathophysiology of diabetic renal injury is multifactorial; however, inflammation and oxidative stress are the main keys in the pathogenesis of the disease [5]. Because induction of diabetes with streptozotocin increases proteinuria and oxidative stress without a change in arterial pressure in Sprague-Dawley rats [6], superimposing streptozotocininduced diabetes on hypertension background could provide a better clinically relevant picture to signs and symptoms of diabetic renal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we have recently demonstrated that diabetic SHR (spontaneously hypertensive rats) are an www.clinsci.org 349 Clinical Science www.clinsci.org excellent experimental model of diabetic renal injury, where diabetes coexists with hypertension and together exacerbate the progression of renal inflammation and injury similar to the clinical manifestations of the disease [7]. The CYP (cytochrome P450) mono-oxygense pathway catalyses the oxidation of arachidonic acid at any of the four double bonds to four regioisomeric EETs (epoxyeicosatrienoic acids) (5,8,11,(12)(13)(14) by the CYP epoxygenase [5,8]. EETs are EDHFs (endothelium-derived hyperpolarizing factors) with anti-hypertensive and anti-inflammatory properties; however, conversion of EET epoxides into their corresponding diols (DHETs) by sEH (soluble epoxide hydrolase) enzyme limits EETs availability and decreases their potential use to combat cardiovascular disease [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, research has shown that EETs exhibit cardiovascular effects and the cellular signaling mechanisms of EETs have been comprehensively reviewed elsewhere (4,6,(8)(9)(10). There is evidence that EETs interact with G protein-coupled receptors to activate intracellular signaling cascades (11)(12)(13); however, an EET receptor has 1 Supported by grants from the National Natural Science Foundation of China (81100085, 81471021, 91439203, and 31130031).…”
Section: Introductionmentioning
confidence: 99%